Explorations in information space knowledge, agents, and organization - Boisot, Max.; MacMillan, Ian C., 1940-; Han, Kyeong Seok.; Oxford eBooks (Oxford : Oxford University Press, 2007)
With the rise of the knowledge economy, the knowledge content of goods and services is going up just as their material content is declining. Economic value is seen to reside in intangible assets, rather than material. This book explores the framework of 'I-Space' - a theoretical approach to the production and distribution of knowledge.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge management; Intellectual capital; Organizational learning; Information superhighway; Intellectual property; Electronic books